Implementasi Model Golden Rules Of User Interface Design Oleh Theo Mandel Pada Aplikasi Diary Sumsel - Gusriani, Moliza; Rohyanti, Sri (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
This study aims to evaluate the interface design of the Sumsel Diary application and find out its strengths and weaknesses using the Golden Rules of User Interface Design model by Theo Mandel. The research method used is a case study supported by literature studies such as scientific journals and books that are in line with the discussion of this article, and reinforced by simple interviews with users of the Sumsel Diary application. The results of the discussion show that the design of the Sumsel Diary application interface can be said to be good, although there are still many shortcomings. This can be seen from the evaluation results with three aspects from Theo Mandel namely, the first aspect positions the user as a control which shows that the Sumsel Diary application is user friendly even though there are deficiencies in collection downloads and supported smartphones. The features and interface display are easy for all users to understand, then finally there is the value of consistency from coloring, layout, positioning of features and menus in the Sumsel Diary application. However, there are also some deficiencies in technical issues and book collections in the application database.